Formation mechanism of the deep double-layer thermal structure in Bohai Bay Basin, eastern China, and its impact on hydrocarbon production - Yubei He; Jian Zhang (Journal of Asian Earth Sciences: X)
Bozhong Depression is the marine part of Bohai Bay Basin and is also the area with the most abundant offshore oil and gas resources in China. According to recent seismic data, kinematic evolution has resulted in a double-layer velocity structure as well as a corresponding double-layer thermal structure in the crust and mantle in Bozhong Depression. Under the influence of the India–Eurasia collision and Pacific plate subduction, Bohai Bay Basin has been subjected to active rifting and associated heat transfers since the late Cenozoic, resulting in two sets of deep and shallow oil and gas reservoir systems, which are related to the double-layer thermal structure. However, the evolution mechanism of this structure remains unclear because of lack of research on the vertical structure of the lithosphere in the area. We conducted finite-element simulations using seismic, geomagnetic, and geothermal heat flow data; results indicate synchronous uplift of deep mantle material and high-temperature crustal material in Bozhong Depression around 23 Ma. Around 5.3 Ma, retreat of the Pacific plate subduction accelerated and the deep mantle was uplifted by a small amount, creating a double-layer structure with differential uplift between the mantle and the crust. Successive synchronous and differential uplift in a double-layer thermal structure explains the anomalously high temperatures found during exploratory drilling in Bozhong Depression. Furthermore, the temperature of the sedimentary stratum in Bozhong Depression currently lies within the best window for oil and gas generation; it is the Golden Age for numerous oil and gas reservoirs.